Writing in the margins: Considerations for safe operating limits. Issue 2 (1st December 2021) - Dee, Sean J.; Ogle, Russell A.; Walters, Matthew S.
Abstract: When learning how to write, school‐age children are often told, "Do not write in the margins." This guidance is important because it instills in a child the sense of where text is best placed on a piece of paper. The same is true for chemical processes—normal operating limits define the area where a process is best operated. However, processes may occasionally stray into the margins beyond the operating limits. As a result, facilities may need to define safety margins where temporary operation beyond the normal operating limits is tolerable. In this paper, guidance will be provided for understanding and setting operating limits and safety margins for chemical processes. Good practices from the industry for defining and setting limits, as well as documenting and communicating the limits to operational staff, will be discussed. Last, a case study that examines safe operating limits, alarm setpoints, interlocks, and process safety information for a dryer processing a thermally unstable material will be presented to illustrate the concepts of the paper.